Bearing-Foreign Material Deposition on Retrieved Co-Cr Femoral Heads: Composition and Morphology. (5th July 2015) - Tikekar, Nishant M.; Heiner, Anneliese D.; Baer, Thomas E.; Kruger, Karen M.; Callaghan, John J.; Brown, Thomas D.; Lannutti, John J.
Abstract : Bearing-foreign material deposition onto a femoral head can occur from contact with an acetabular shell due to dislocation, reduction, or subluxation. The purpose of this study was to comprehensively characterize deposit regions on retrieved cobalt-chrome femoral heads from metal-on-polyethylene total hip arthroplasties that had experienced such adverse events. The morphology, topography, and composition of deposition regions were characterized using macrophotography, optical profilometry, scanning electron microscopy, energy dispersive spectroscopy, and X-ray photoelectron spectroscopy. The deposit areas were relatively large, they were much rougher than the surrounding undamaged clean areas, and they displayed several distinct morphologies. Titanium alloy elements were the predominant constituents. Calcium and phosphorous were also detected within the deposit areas, in a composition that could nucleate abrasive hydroxyapatite. In addition, tungsten-rich particles, likely present as tungsten carbide, were observed on top of the titanium deposits. The increased roughness associated with these deposition features would be expected to accelerate damage and wear of the opposing liner and hence accelerate the development of osteolysis.